2016
DOI: 10.1093/dnares/dsw038
|View full text |Cite
|
Sign up to set email alerts
|

Artifactual mutations resulting from DNA lesions limit detection levels in ultrasensitive sequencing applications

Abstract: The need in cancer research or evolutionary biology to detect rare mutations or variants present at very low frequencies (<10−5) poses an increasing demand on lowering the detection limits of available methods. Here we demonstrated that amplifiable DNA lesions introduce important error sources in ultrasensitive technologies such as single molecule PCR (smPCR) applications (e.g. droplet-digital PCR), or next-generation sequencing (NGS) based methods. Using templates with known amplifiable lesions (8-oxoguanine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 61 publications
1
62
0
Order By: Relevance
“…Our data show that rare mutation frequencies are significantly lower in DCS analysis in comparison to NGS and SSCS analyses, suggesting that large number of rare mutations detected by NGS and SSCS are mostly artifacts (Figure 3A). Particularly, C>A/G>T transversions, which have been previously reported to be a predominant result of DNA oxidation [11,16], showed the greatest decrease in frequencies with DCS analyses of Duplex Sequencing (Figure 3J,K). These findings validate that DCS can identify and correct artifacts and be applied for accurately detecting rarely occurring mutations.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Our data show that rare mutation frequencies are significantly lower in DCS analysis in comparison to NGS and SSCS analyses, suggesting that large number of rare mutations detected by NGS and SSCS are mostly artifacts (Figure 3A). Particularly, C>A/G>T transversions, which have been previously reported to be a predominant result of DNA oxidation [11,16], showed the greatest decrease in frequencies with DCS analyses of Duplex Sequencing (Figure 3J,K). These findings validate that DCS can identify and correct artifacts and be applied for accurately detecting rarely occurring mutations.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, we identified the heat-induced artifactual mutations. Although Duplex Sequencing has been used in a previous study to show an increased level of mutation frequency of small selected regions of nuclear genome in DNA incubated at 65°C [11], the same temperature used in this study, exact identities of the heat-induced artifactual mutations have not been presented. Moreover, while types of artifactual mutations have been previously examined, influences of neighboring nucleotide base context on artifactual mutations have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, COLD-ddPCR has been demonstrated to easily and rapidly detect multiple mutations and identify unknown variants in the target sequences. In 2016, Arbeithuber et al [59] demonstrated that DNA repair enzymes could reduce the artificial mutations caused by long heat incubation and the subsequent error in ultrasensitive technologies such as ddPCR. This finding provides direction in optimizing dPCR performance.…”
Section: Perspectivesmentioning
confidence: 99%